Multi-scale morphological gradient algorithm based ultra-high-speed directional transmission line protection for internal and external fault discrimination - Elmahdi Khoudry; Abdelaziz Belfqih; Tayeb Ouaderhman; Jamal Boukherouaa; Faissal Elmariami (Institute of Advanced Engineering and Science, 2019)
This paper introduces an ultra-high-speed directional transmission line protection scheme based on multi-scale morphological gradient algorithm (MSMGA). The directional protection scheme sets down the rules for determining the fault position in relation to the relaying point. The MSMGA is used to extract the fault-induced transient characteristics contained in the voltage and current signals. The associated signals are formed from these transient characteristics and the polarity of their local modulus maxima allow the discrimination between internal and external faults.